Business data communications and networking - FitzGerald, Jerry, 1936-; Durcikova, Alexandra (Hoboken, NJ : Wiley, 2015)
'Over the past few years, many fundamental changes have occurred in data, communication, and networking that will shape the future for decades to come. Updated with the latest advances in the field, Jerry FitzGerald, Alan Dennis and Alexandra Durcikova's 12th Edition of Business Data Communications and Networking continues to provide the fundamental concepts and cutting-edge coverage of applications that students need to succeed in this dynamic field. Authors FitzGerald, Dennis and Durcikova have developed a foundation and balanced presentation from which new technologies and applications can be easily understood, evaluated, and compared'--
Machine generated contents note: Chapter 1 Introduction to Data Communications 1.1 Introduction 1.2 Data Communications Networks 1.3 Network Models 1.4 Network Standards 1.5 Future Trends 1.6 Implications for Management Chapter 2 Application Layer 2.1 Introduction 2.2 Application Architectures 2.3 World Wide Web 2.4 Electronic Mail 2.5 Other applications 2.6 Implications for Management Chapter 3 Physical Layer 3.1 Introduction 3.2 Circuits 3.3 Communication Media 3.4 Digital Transmission of Digital Data 3.5 Analog Transmission of Digital 3.6 Digital Transmission of Analog Data 3.7 Implications for Management Chapter 4 Data Link Layer 4.1 Introduction 4.2 Media Access Control 4.3 Error Control 4.4 Data Link Protocols 4.5 Transmission Efficiency 4.6 Implications for Management Chapter 5 Network and Transport Layers 5.1 Introduction 5.2 Transport and Network Layer Protocols 5.3 Transport Layer Functions 5.4 Addressing 5.5 Routing 5.6 TCP/IP Example 5.7 Implications for Management Chapter 6 Network Design 6.1 Introduction 6.2 Needs Analysis 6.3 Technology Design 6.4 Cost Assessment 6.5 Implications for Management Chapter 7 Wired and Wireless Local Area Networks 7.1 Introduction 7.2 LAN Components 7.3 Wired Ethernet 7.4 Wireless Ethernet 7.5 The Best Practice LAN Design 7.6 Improving LAN Performance 7.7 Implications for Management Chapter 8 Backbone Networks 8.1 Introduction 8.2 Switched Backbone 8.3 Routed Backbones 8.4 Virtual LANs 8.5 The Best Practice Backbone Design 8.6 Improving Backbone Performance 8.7 Implications for Management Chapter 9 Wide Area Networks 9.1 Introduction 9.2 Dedicated-Circuit Networks 9.3 Packet-Switched Networks 9.4 Virtual Private Networks 9.5 The Best Practice WAN Design 9.6 Improving WAN Performance 9.7 Implications for Management Chapter 10 The Internet 10.1 Introduction 10.2 How the Internet Works 10.3 Internet Access Technologies 10.4 The Future of the Internet 10.5 Implications for Management Chapter 11 Network Security 11.1 Introduction 11.2 Risk Assessment 11.3 Ensuring Business Continuity 11.4 Intrusion Prevention 11.5 Best Practice Recommendations 11.6 Implications for Management Chapter 12 Network Management 12.1 Introduction 12.2 Designing for Network Performance 12.3 Configuration Management 12.4 Performance and Fault Management 12.5 End User Support 12.6 Cost Management 12.7 Implications for Management .
Includes bibliographical references and index.
Keywords: Data transmission systems; Computer networks; Office practice -- Automation